Neuropilin-2b facilitates resistance to tyrosine kinase inhibitors in non-small cell lung cancer - Dimou, Anastasios; Nasarre, Cecile; Peterson, Yuri K; Pagano, Rose; Gooz, Monika; Nasarre, Patrick; Drabkin, Harry A; Armeson, Kent E; Gibney, Barry C; Gemmill, Robert M; Denlinger, Chadrick E (The Journal of thoracic and cardiovascular surgery, 2021)
Innate and acquired resistance is the principle factor limiting the efficacy of tyrosine kinase inhibitors in lung cancer. We have observed a dramatic upregulation of the cell surface co-receptor neuropilin-2b in lung cancers clinically treated with tyrosine kinase inhibitors correlating with acquired resistance. We hypothesize that neuropilin-2b plays a functional role in acquired tyrosine kinase inhibitor resistance. Non-small cell lung cancer proliferation and survival were determined during chronic tyrosine kinase inhibitor exposure in the presence or absence of neuropilin-2b knock-down. Interactions of neuropilin-2a and neuropilin-2b isoforms with PTEN and GSK3β were assessed by immunoprecipitation. Neuropilin-2a and neuropilin-2b mutants deleted for their cytoplasmic domains were used to identify regions responsible for neuropilin-2b-GSK3β interaction. Because GSK3β is known to phosphorylate and degrade PTEN, phospho-PTEN and total PTEN levels were assessed after transfection of neuropilin-2a and neuropilin-2b wild-type and mutant constructs. Non-small cell lung cancer cells chronically treated with gefitinib or osimertinib developed drug resistance and exhibited logarithmic growth in the presence of endothelial growth factor receptor tyrosine kinase inhibitors. However, neuropilin-2b knockdown cells remained sensitive to gefitinib. Likewise, neuropilin-2b knockdown suppressed and neuropilin-2a knockdown enhanced cellular migration. Acquired drug resistance and cell migration correlated with neuropilin-2b-dependent AKT activation with the intermediate step of GSK3β-dependent PTEN degradation. A specific binding site for GSK3β on the cytoplasmic domain of neuropilin-2b was identified with truncated protein constructs and computer modeling. Neuropilin-2b facilitates non-small cell lung cancer resistance to tyrosine kinase inhibitors, and this biological effect relates to AKT activation. Neuropilin-2b GSK3β interactions appear to be essential for PTEN degradation and AKT activation in lung cancer cells. Disruption of the neuropilin-2b GSK3β interaction may represent a novel treatment strategy to preserve sensitivity to tyrosine kinase inhibitors in non-small cell lung cancer.